Transcultural pilot study of the efficacy of reminiscence therapy for mexican and spanish older adults with different levels of cognitive decline - Villasán Rueda, Alba; Sánchez Cabaco, Antonio; Mejía Ramírez, Manuel Alejandro; Marina Afonso, Rosa; Castillo Riedel, Eduardo (My University, 2023)
The main objective for this study is to analyze the impact of a positive reminiscence therapy program (REMPOS) in cognitive functioning and depressive symptomatology for older adults in different vital situations (healthy aging, mild cognitive impairment, and Alzheimer’s disease). This is a transcultural comparative study (older people from Spain and Mexico). A randomized design with pre-posttest measurement and twelve groups was formulated, during a period of six months of intervention (3 in Mexico and 3 in Spain). The design had: 6 experimental groups with REMPOS intervention (3 in Mexico and 3 in Spain) during a period of six months and 6 control groups that received cognitive stimulation. While a key aspect of this study is the cross-cultural differences, an important part is to determine whether each experimental group had similar results in terms of the change in magnitude between the pre and post analysis. In general, intervention significantly improved cognitive function and decreased depressive symptoms. These findings provide further evidence about the efficacy of the REMPOS therapy between different types of aging and both geographical and cultural contexts (Spain and Mexico).
Journal of Cross-Cultural Gerontology
Keywords: Aging; Cognitive stimulation; Depressive symptomatology; Memory and reminiscence; Campus Tijuana